Impact of reporting format of unrealized gain or loss of equity investment on investors’ risk perception - Chin Yee Gan; Zauwiyah Ahmad; Lee Lee Chong (Cogent Business & Management)
The purpose of this study is to investigate how the presentation of unrealized gain or loss of equity investment not held for trading purposes, moderated by the volatilities of unrealized gain or loss of such equity investment and stability of share price, affect investors’ risk perception. This study used an experimental approach with a psychology framework to explore the research objectives. The finding demonstrates that volatility of unrealized gain or loss of equity investments influences investors’ risk perception when it is presented in a profit or loss statement given that the share price trend is stable. Similarly, when unrealized gain or loss was non-volatile and unrealized gain or loss of such equity investments was presented in the profit or loss statement, investors will focus on stability of share price when assessing the risk of the company.